Glioblastoma in pregnancy: A case report - Bram Pradipta; Cut M. Yeni (Syiah Kuala University, 2012)
Incidence of primary intracranial tumour in pregnancy is very rare. This rare association is becoming more common because women in developed societies defer childbearing to the third or fourth decade of life. We presented A case of a 33- year-old, gravida 2 para 1, Indonesian Acehnese women presented with pregnancy and recurrent Glioblastoma. Her chief complaint was headache that is worsening since 1 month ago. She is a patient of Neurosurgery Department since 7 months earlier with complaints of major headache, vomitting, seizure and weakness of the left part of her body when she was 12 weeks pregnant. Patients was diagnosed with brain tumor on right temporoparietal region. Her CT scan result are midline shift to the left of falx cerebri with obliterated right ventricle and hypodens mass on right region size 5,04x 5,17 cm x 5,79 cm. Craniotomy was performed with no regards of the pregnancy but the patient refuse to terminate the pregnancy. Post craniotomy patient was supposed to undergo series of radiotherapy but decided not to since it may complicate her pregnancy. After 5 month went untreated, patient then had another CT scan due to her recurring complaint and the result was there’s an area of hypo and hyperdens in fronto parietal dextra and sinistra with brain edema. The patient was treated for a week when her condition was worsening with loss of consciousness. We then perfomed joint operation with Neurosurgery dept consist of Cesarean section that was continued with craniotomy where we delivered a heathy 1900 gram baby boy. The patient was then treated for 2 days in the intensive care unit and another 4 days in the ward then discharged home in good condition. Every brain tumours in pregnancy bring dilemmas with no standard treatment in medicine. Its diagnosis is challenging because of the need to treat the mother and minimizing the effects of cancer treatment on the fetus. The treatment intention is to minimise mortality and morbidity for both maternal and fetal which can be achieved by prolonging pregnancy while alleviating complications from the brain tumour. The management have to be individualised from a multi-disciplinary team and the consideration of a multitude of factors, including nature and location of the tumour, associated signs and symptoms, fetal gestation and the patient’s wishes.